The apelinergic system: a perspective on challenges and opportunities in cardiovascular and metabolic disorders. Issue 1 (25th June 2019) - Marsault, Eric; Llorens‐Cortes, Catherine; Iturrioz, Xavier; Chun, Hyung J.; Lesur, Olivier; Oudit, Gavin Y.; Auger‐Messier, Mannix
Abstract: The apelinergic pathway has been generating increasing interest in the past few years for its potential as a therapeutic target in several conditions associated with the cardiovascular and metabolic systems. Indeed, preclinical and, more recently, clinical evidence both point to this G protein–coupled receptor as a target of interest in the treatment of not only cardiovascular disorders such as heart failure, pulmonary arterial hypertension, atherosclerosis, or septic shock, but also of additional conditions such as water retention/hyponatremic disorders, type 2 diabetes, and preeclampsia. While it is a peculiar system with its two classes of endogenous ligand, the apelins and Elabela, its intricacies are a matter of continuing investigation to finely pinpoint its potential and how it enables crosstalk between the vasculature and organ systems of interest. In this perspective article, we first review the current knowledge on the role of the apelinergic pathway in the above systems, as well as the associated therapeutic indications and existing pharmacological tools. We also offer a perspective on the challenges and potential ahead to advance the apelinergic system as a target for therapeutic intervention in several key areas. Abstract : This perspective article reviews current knowledge on the role of the apelinergic pathway in the cardiovascular and metabolic systems and discusses recent evidence pointing to this G protein–coupled receptor as a target of interest in the treatment of not only cardiovascular disorders, but also of conditions such as water retention/hyponatremic disorders, type 2 diabetes, and preeclampsia.